2019
DOI: 10.1101/834556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple evidences suggest sox2 as the main driver of a young and complex sex determining ZW/ZZ system in turbot (Scophthalmus maximus)

Abstract: A major challenge in evolutionary biology is to find an explanation for the variation in sex-determining (SD) systems across taxa and to understand the mechanisms driving sex chromosome differentiation. We studied the turbot, holding a ZW/ZZ SD system and no sex chromosome heteromorphism, by combining classical genetics and genomics approaches to disentangle the genetic architecture of this trait. RAD-Seq was used to genotype 18,214 SNPs on 1,135 fish from 36 families and a genome wide association study (GWAS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 84 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…Further, gene expression and knockout studies supported dmrt1 function as a master SD gene in C. semilaevis Cui et al, 2017). Novel and unexpected SD genes have been recently reported in other Carangaria species such as sox2 in Scophthalmus maximus from the order Pleuronectiformes, in which the only diagnostic variant detected between Z and W chromosomes can be located on the regulatory element of sox2 leading to differential expression through a complex regulation of this gene involving a lncRNA (Martínez et al, 2019). Similarly, a missense SNP in the third exon of the gene encoding the steroidogenic enzyme 17β-hydroxysteroid dehydrogenase 1 (Hsd17b1) was perfectly associated with ZZ/ZW sex determination in yellowtail amberjack Seriola lalandi, from the order Carangiformes, whereas Z alleles (containing the less enzymatically effective Glu144 or Lys144) cause silencing of the steroid conversion during sex differentiation, leading to a shortage of E2 and establishement of testis (Koyama et al, 2019).…”
Section: Percomorpha: Carangariamentioning
confidence: 78%
“…Further, gene expression and knockout studies supported dmrt1 function as a master SD gene in C. semilaevis Cui et al, 2017). Novel and unexpected SD genes have been recently reported in other Carangaria species such as sox2 in Scophthalmus maximus from the order Pleuronectiformes, in which the only diagnostic variant detected between Z and W chromosomes can be located on the regulatory element of sox2 leading to differential expression through a complex regulation of this gene involving a lncRNA (Martínez et al, 2019). Similarly, a missense SNP in the third exon of the gene encoding the steroidogenic enzyme 17β-hydroxysteroid dehydrogenase 1 (Hsd17b1) was perfectly associated with ZZ/ZW sex determination in yellowtail amberjack Seriola lalandi, from the order Carangiformes, whereas Z alleles (containing the less enzymatically effective Glu144 or Lys144) cause silencing of the steroid conversion during sex differentiation, leading to a shortage of E2 and establishement of testis (Koyama et al, 2019).…”
Section: Percomorpha: Carangariamentioning
confidence: 78%
“…sox3 is the male-determining factor on the Y chromosome in the fish Oryzias dancena ( Takehana et al, 2014 ), while it was found mainly expressed in the ovaries of yellowfin seabream ( Acanthopagrus latus ) ( Li et al, 2020 ). In addition, sox2 is the master sex determination gene in turbot ( Martínez et al, 2019 ). Notably, the sox9 gene, a major transcription factor in testicular development, has been widely studied in various fish species, for example, rainbow trout and Japanese flounder ( Paralichthys olivaceus ) ( Baron et al, 2005 ; Raghuveer and Senthilkumaran, 2010 ; Li et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research in teleosts has unveiled ASE patterns in response to various environmental factors. In the case of turbot (Scophthalmus maximus), SNP studies discovered the sex determination patterns of ASE 45 . Similarly, SNP markers in Atlantic salmon (Salmo salar) were found to enhance DHA synthesis 46 , while eQTL were associated with resistance to lice in Atlantic salmon 47 and broad scale suppression of gene expression was detected in triploid medaka (Oryzias latipes) 48 .…”
Section: Many Different Reasons Can Explain This Variable Expression ...mentioning
confidence: 99%